2014
DOI: 10.1590/0004-2730000002654
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of glucose metabolism disturbances in Chinese Muslims and possible risk factors: a study from northwest China

Abstract: (PDM) in the Muslim population in northwest China, and discuss the risk factor. Materials and methods: According to the income and the population, we randomly selected 3 villages with stratified and cluster sampling. The subjects were residents ≥ 20 years of age, and were from families which have been local for > 3 generations. The questionnaire and oral glucose tolerance test (OGTT) were completed and analyzed for 660 subjects. Results: The prevalence of DM and PDM between the Han and Muslim populations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The higher distribution of subjects with C-IFG/IGT in this study is not similar to the distributions reported by studies performed in other Asian countries [12,16]. For example, I-IFG subtype is higher than other subtypes in Japan [17], whereas, in China, I-IGT subtype is the highest [18]. It is not clear whether this discrepancy reflects ethnic differences between studies, or whether this result was due to a small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…The higher distribution of subjects with C-IFG/IGT in this study is not similar to the distributions reported by studies performed in other Asian countries [12,16]. For example, I-IFG subtype is higher than other subtypes in Japan [17], whereas, in China, I-IGT subtype is the highest [18]. It is not clear whether this discrepancy reflects ethnic differences between studies, or whether this result was due to a small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…In total, there were 19 studies using the WHO 1999 classification, of which eight studies focused on Caucasians [ 44 , 47 , 76 , 77 , 79 , 80 , 81 , 84 ] and 11 on Asians [ 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 71 , 74 , 81 ] ( Table 2 ). Fourteen studies utilised the ADA 2003 classification, with seven Caucasian [ 44 , 47 , 75 , 77 , 78 , 79 , 80 ] and seven Asian studies [ 61 , 63 , 65 , 68 , 70 , 72 , 73 ] ( Table 3 ). There were a total of 32,204 individuals classified with prediabetes from 19 studies ( Table 2 ), of which 10,999 were Caucasian (eight studies) and 21,205 were Asian (11 studies), based on the WHO 1999 classification; and 27,112 individuals classified with prediabetes from 14 studies ( Table 3 ), of which 11,744 were Caucasian (seven studies) and 15,765 were Asian (seven studies) based on the ADA 2003 classification.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 articles included, six reported on Chinese cohorts [ 61 , 62 , 63 , 64 , 65 , 66 ], three Indian cohorts [ 67 , 68 , 69 ], two Malaysian [ 70 , 71 ], one Thai [ 72 ], and one Korean cohort [ 73 ]. All were classified as Asian ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, genetic factors determine the development of both obesity and T2DM by influencing taste, food preferences and dietary patterns, sedentary lifestyle, as well as basal metabolism and calories burn [13]. Additional risk factors of T2DM include age, smoking, stress, sleep disorders and depression [14][15][16]. Further clinical risk factors associated with T2DM development include abdominovisceral obesity, hyperglycemia, hypertension and dyslipidaemia, i.e.…”
Section: Introductionmentioning
confidence: 99%